Recent clinical evidence on nutrition, novel pharmacotherapy, and vaccination in inflammatory bowel diseases - Gheonea, Theodora; Bogdan, Maria; Meca, Andreea-Daniela; Rogoveanu, Ion; Oancea, Carmen (Frontiers in Pharmacology, 2024)
Inflammatory bowel diseases (IBD), which enclose Crohn's disease (CD) and ulcerative colitis (UC), are chronic, relapsing inflammatory ailments. Their specific pathogenesis is not completely clarified, the worldwide incidence and prevalence of IBD has been steadily growing, and there is still not a definitive cure. The management of IBD has become more and more targeted, with specific immune mediators identified to be involved in its pathogenesis. Vedolizumab, a humanised monoclonal antibody binding specifically to the α4β7 integrin, is a gut-selective immunosuppressive biologic drug administered for both CD and UC. With the same indications as vedolizumab, ustekinumab is a fully human IgG1κ monoclonal antibody binding with specificity to the shared p40 protein subunit of human cytokines interleukin (IL)-12 and IL-23. Several selective IL-23p19 monoclonal antibodies (risankizumab, mirikizumab, and guselkumab) have also revealed admirable efficacy and safety in IBD patients. Nutrition is a very important environmental factor associated with the onset and progression of IBD, and the Western diet is considered to contribute to the development of IBD. In this narrative review, our aim is to present an overview of the main results from recent clinical studies on IBD regarding diet, new drug treatments, and also vaccination.